Analisis Makna Konotasi Pada Karya Desain Komunikasi Visual - Susi Handayani (Universitas Bumigora, 2021)
The activity of exploring messages and meanings in design work is an important part of understanding the concept of design thinking that is reflected in his work. Each message that is presented in the work is the essence of a design outside of the formalistic factors of form as can be seen by the eye. To explore more deeply about the essence of visual massage in design work, the authors use a collaborative method using semiotic science studies techniques that focus on the image of the visual element and the connotation meaning in it. The process of collecting data in this study starts from several important stages, such as observation, interviews, documentation to preparing a literature review. data analysis techniques in this paper, using several stages such as, collecting data, reducing data, analyzing and drawing conclusions. The semiotic study is the choice of analysis because the characteristics of the semiotic study are still relevant in interpreting the signs and meanings poured out by the designer in his work. The concept of the creation of three public service announcements is the study in this paper. Has the same concept in the effort to provide information, instructions and persuade the audience to re-view nature as an ecosystem that must be preserved and maintained, even though it uses different idioms